"Father to my story": writing Foe, de-authorizing (De)Foe - Almagro Jiménez, Manuel (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2005)
Foe is probably not J.M. Coetzee's best known novel, although it is a text of great importance because of the way in which its political, literary and theoretical values are interrelated. The novel addresses a foundational myth of Western societies in the figure of Robinson Crusoe, and draws attention to its textual quality. This concern with the process of representation and the narrative quality of our beliefs is also manifested throughout the novel in other issues. Thus, in the text there is a whole panoply of reflections about the central issues affecting the very mechanics of constructing a text, such as, for example, the proper way a story should be written, the relationship between representation and its referent in the real, the problem of realism, or the question of authorship.